PERENCANAAN ALAT ANGKAT KENDARAAN NIAGA KAPASITAS 2 TON - Hiskia Goni; Jan Soukotta; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
Equipment design start from component design. In order to meet the requirements, it is designed base on the material used. The purpose of this study is to design a manually operated lifting equipment of 2 ton capacity used in a commercial vehicles in the form of engineering drawing. Comparison data used in this study is a triple lift floor jack. From the calculations, it is found that the largest load happened a lifting position. Keywords: lift equipment, commercial vehicle, 2 ton manual lifting equipment